The Relationship Between the Role of the Nurse and the Level of Anxiety in Preoperative Fracture Patients at Dr. Wahidin Sudirohusodo Makassar - Salam, La Ode Nuh (ScieClouds Publishing, 2023)
The preoperative situation is a condition that can cause anxiety. Reducing anxiety is an important thing for nurses to do because physical and emotional stress can increase the risk of surgery. The aim of the research is to determine the relationship between the role of nurses and the level of anxiety for fracture surgery patients. The research method used is a cross sectional method with a sampling technique using total sampling . The sample studied was 35 respondents who were treated in the Lontara II treatment room in the Orthopedics section of RSUP DR. Wahidin Sudirohusodo Makassar from April 18 to May 14 2009. Data was collected using a questionnaire and Chi Square statistical test analysis was carried out with a significance level aof ≤ 0.05. Based on the relationship test, it was found that the statistical p value = 0.002 ≤ 0.05 , which means that there is a fairly strong relationship between the role of preoperative nurses and a reduction in anxiety levels. In this study, clients with fractures who were about to undergo surgery received preoperative care , however the number/quantity of nursing roles given to patients was not optimal as expected, and from the results of the study it was concluded that the inadequate role of nurses in preoperative patients would affect the patient's anxiety level. Based on the description above, it is important for nurses to maintain and increase their role in providing preoperative care and pay attention to the client's preoperative anxiety level. Increasing the quantity and quality of preoperative nursing services involving physical, psychological, social and spiritual aspects. It is necessary to develop/research a standard procedure that allows treatment to reduce/reduce anxiety in preoperative nursing clients.